2011
DOI: 10.5505/1304.7361.2011.26213
|View full text |Cite
|
Sign up to set email alerts
|

Glass Related Hand and Wrist Injury: Accidental or Sudden Anger

Abstract: AmaçTravmatik el ve el bileği yaralanmaları acil serviste yaygın görülen yaralanmalardır. Ani öfkelenmeye bağlı cama yumruk atma ile ilişkili el ve el bileği yaralanmaları ülkemizde sıktır. Bu çalışmanın amacı oluş nedenlerine göre cam kesisi ile ilişkili el ve el bileği yaralanmalı hastalarda klinik ve demografik özellikleri analiz etmektir. Gereç ve Yöntem Dicle Üniversitesi Tıp Fakültesi Acil Servisi'ne cam kesisine bağlı yaralanma nedeniyle başvuran hastalar çalışmaya dahil edildi. Hastaların demografik ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…This may be attributed to the large number of university students in our study. damaging the wrist area in particular as the fist is being withdrawn (9). From that perspective, our results are valuable in terms of showing anatomical zones affected by glass-punching injuries.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…This may be attributed to the large number of university students in our study. damaging the wrist area in particular as the fist is being withdrawn (9). From that perspective, our results are valuable in terms of showing anatomical zones affected by glass-punching injuries.…”
Section: Discussionmentioning
confidence: 79%
“…The hand that patients employ to strike these objects is normally the dominant hand used in normal life (9,17,18). Studies have reported that glass-punching often occurs in the home or in public places, and that the incidence increases on special occasions, such as match finals, weekends, New Year's, or birthdays (2,9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations